2012
DOI: 10.1111/j.1432-2277.2012.01468.x
|View full text |Cite
|
Sign up to set email alerts
|

An overview of renal replacement therapy and health care personnel deficiencies in sub-Saharan Africa

Abstract: Summary Chronic kidney disease (CKD) is a public health problem in sub‐Saharan Africa (SSA) but there is limited data to guide programs or plan interventions. To help set priorities and understand the needs for renal replacement therapy a baseline assessment is required. World Health Organization (WHO) databases and Medline were searched to determine the number of physicians, nephrologists, and dialysis centers and patients in SSA. Data on renal transplant (RTx) programs were collected from the WHO Global Obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Nigeria has the third highest number (6.3 per million population) of patients on hemodialysis after South Africa and Kenya. 10 Recently, there has been a proliferation of dialysis centers in Nigeria, owned by both private individuals and the government.…”
Section: Introductionmentioning
confidence: 99%
“…Nigeria has the third highest number (6.3 per million population) of patients on hemodialysis after South Africa and Kenya. 10 Recently, there has been a proliferation of dialysis centers in Nigeria, owned by both private individuals and the government.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is true that Mauritius has far more nephrologists per million population (npmp) than the countries in sub-Saharan Africa, previous published figures of 10 npmp in 2012 and 8 npmp in 2015 are clear overestimates (12,13,14). The actual figure for 2020 is 7.5 npmp and was far lower previously (see Figure 2).…”
Section: Nephrology Workforcementioning
confidence: 99%
“…El Matri et al demonstrated in 2008 that renal transplantation is performed in 10 of the 53 countries, and only 5 countries (Egypt, South Africa, Tunisia, Algeria, and Sudan) have sustained programs that perform more than 50 cases per year [10]. In 2012, Pozo et al demonstrated that in the 47 sub-Saharan African countries, Kenya, Nigeria, and South Africa were the only countries with renal transplantation programs and reported rates per million population of 0.60, 0.23, and 5.12, respectively [11], Table 2.…”
Section: Kidney Transplantation In Sub-saharan Africamentioning
confidence: 99%